Exceeding Hardware Confined Bandwidth in Incoherent Optical Frequency Domain Reflectometry - Härteis, Lisa-Sophie; Renner, Esther; Schmauß, Bernhard (2022 IEEE Photonics Conference, IPC 2022 - Proceedings, 2022)
Bidirectional incoherent optical frequency domain reflectometry exhibits confined spatial resolution through the Mach-Zehnder Modulator's restricted bandwidth in backward direction. We propose hardware confined bandwidth exceedance by utilizing digital signal processing and therewith improve the spatial resolution by a factor of four.
CRIS-Team Scopus Importer:2024-12-16
Keywords: electrical bandwidth; fiber Bragg gratings; OFDR; signal processing; spatial resolution